A Study of Identification of Capital Budgeting Tools applied in Investment Decision - Dr. Madhuri Kadam,; Dr. Neetu Singh, (The Bioscan, 2025)
A study of the identification of capital budgeting tools applied in investment decisions is crucial as it provides insights into the financial methodologies and practices that firms employ to evaluate and prioritize their long-term investment projects. By understanding which tools are most effective in forecasting returns, assessing risks, and optimizing resource allocation, companies can make more informed and strategic decisions, ultimately enhancing their financial performance and competitive edge. Such a study also helps in identifying gaps and opportunities for improving decision-making processes, ensuring that investments contribute positively to the firm's growth and sustainability.